2011
DOI: 10.1590/s0103-64402011000300002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of instrumentation using curettes, piezoelectric ultrasonic scaler and Er,Cr:YSGG laser on the morphology and adhesion of blood components on root surfaces: a SEM study

Abstract: This study used scanning electron microscopy (SEM) to evaluate the morphology and adhesion of blood components on root surfaces instrumented by curettes, piezoelectric ultrasonic scaler and Er,Cr:YSGG laser. One hundred samples from 25 teeth were divided into 5 groups: 1) Curettes; 2) Piezoelectric ultrasonic scaler; 3) Curettes plus piezoelectric ultrasonic scaler; 4) Er,Cr:YSGG laser; 5) Curettes plus Er,Cr:YSGG laser. Ten samples from each group were used for analysis of root morphology and the other 10 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
(37 reference statements)
1
16
1
Order By: Relevance
“…In our study, after analysing the MRS of the samples after the treatments, it was observed that the root surfaces treated with MC exhibited a smooth surface with occluded dentinal tubules and the presence of a smear layer, and this morphology pattern resembles those found in other studies . This morphological aspect is due to the extensive contact area between the cutting face of the MC and the sample, which facilitates the achievement of a root surface that is more uniform and regular .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, after analysing the MRS of the samples after the treatments, it was observed that the root surfaces treated with MC exhibited a smooth surface with occluded dentinal tubules and the presence of a smear layer, and this morphology pattern resembles those found in other studies . This morphological aspect is due to the extensive contact area between the cutting face of the MC and the sample, which facilitates the achievement of a root surface that is more uniform and regular .…”
Section: Discussionmentioning
confidence: 99%
“… and Tsurumaki et al. , determined that although Er,Cr:YSGG laser irradiation produced rougher root surfaces than treatment with scaling and root planing, there was no significant difference between treatments regarding adhesion of blood components. Therefore, three of four in vitro studies suggest that treatment with the Er:YAG laser, the Er,Cr:YSGG laser or the diode laser (one study) has little impact on adherence of blood components to laser‐irradiated root surfaces.…”
Section: The Nd:yag Laser (Not Lanap®) and Treatment Of Periodontitismentioning
confidence: 99%
“…With respect to the phenomenon of laser‐induced fibrin sealing of periodontal pockets, it is interesting to note that only four in vitro studies and no in vivo studies could be identified as having studied the impact of various modes of root surface treatment on the adherence of blood components . Theodoro et al.…”
Section: The Nd:yag Laser (Not Lanap®) and Treatment Of Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…Root surface conditioning of a tooth affected by periodontal disease aims to remove dental calculus, bacterial biofims and their toxins 2,[8][9] , which consequently contributes to a reduced inflammatory process, periodontal tissue repair [10][11][12] including formation of new supporting tissues [12][13][14] . However, mechanical debridement procedures are known to create a layer of organic, mineralized waste, also known as smear layer, which covers the prepared root surface and obstructs the dentinal tubules [14][15] , serving as substrate for bacterial growth and making periodontal attachment to the root surface more difficult 11 . Therefore, an alternative method to remove the smear layer is the combination of debridment and chemical root conditioning, which may be capable of decontaminating, detoxifying and demineralizing the root surface, thus opening the dentinal tubules and exposing the collagen matrix 2,[11][12][13][14]16 , which is fundamental for recolonization of cells involved in periodontal repair 2,[10][11][12]14 , promoting a urface that is biologically compatible with both epithelial and connective issues 2,12,14,[17][18] .…”
Section: Introductionmentioning
confidence: 99%